Insulating adhesive, photovoltaic module and preparation method thereof
Patent Information
- Application Number
- CN202611393122.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-09
- Publication Date
- 2026-10-30
AI Technical Summary
该方法具有交联密度高,机械强度好的特点,但是存在固化时间长(分钟级)、与BC电池高速产线节拍不匹配,存在1-5%的固化收缩率易导致电池片翘曲的问题;另一类是UV光固化丙烯酸绝缘胶:以聚氨酯丙烯酸酯等光敏树脂为主体,在紫外光照射下通过自由基聚合在数秒内完成固化
[0077](1)本申请提供的绝缘胶采用嵌段共聚物和/或高低Tg树脂共混体系作为主体树脂,该材料在固化时收缩率更低,克服了传统环氧绝缘胶在无填料或低填料条件下因固化收缩率高(1%-5%)、应力增大而导致的翘曲问题;另外,本申请中高Tg树脂在室温下提供足够的内聚强度和触变性,支持高精度丝网印刷,低Tg树脂可实现在层压高温下应力松弛与界面贴合增强,进一步提高界面的附着力。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This application relates to the field of photovoltaic technology, and in particular to an insulating adhesive, a photovoltaic module, and a method for preparing the same. Background Technology
[0002] BC cells place all electrodes (positive and negative) on the back of the cell to maximize the light-receiving area on the front. While this design improves photoelectric conversion efficiency (LONGi HBC cells have achieved an efficiency of 27.30%), it also brings new technical challenges: 1. Extremely small spacing between positive and negative electrodes: The P and N regions on the back are arranged in an interdigitated pattern, with a spacing of only 0.5-2mm; 2. Insulation requirements for string bonding: When modules are connected in series, the solder ribbons need to cross different polarity regions, and insulating adhesive must be applied at specific locations to prevent short circuits; 3. Process temperature resistance: The insulating adhesive must withstand the instantaneous high temperature (200-250℃, 3-5 seconds) of the string bonding process without softening or decomposing.
[0003] Currently, the industry commonly uses two main types of single-curing system insulating adhesives: One type is thermosetting epoxy insulating adhesive: based on epoxy resin, it is cured by heating (usually 150-180℃, 5-10 minutes) to initiate ring-opening crosslinking of epoxy groups. This method features high crosslinking density and good mechanical strength, but suffers from long curing times (minutes), mismatch with the high-speed production cycle of BC batteries, and a 1-5% curing shrinkage rate that can easily lead to cell warping. The other type is UV-cured acrylic insulating adhesive: based on photosensitive resins such as polyurethane acrylate, it is cured within seconds through free radical polymerization under ultraviolet light. This process features extremely fast curing speed (≤10 seconds), adaptability to high-speed production cycles, and acceptable initial peel strength, but still suffers from severe adhesion degradation after aging, and low peel strength due to the adhesive's inability to fully fill the interface on the uneven back of the BC battery.
[0004] The back of BC batteries has an uneven microstructure (such as pyramidal texture, passivation layer texture, and battery grid). Traditional UV-cured insulating adhesives are difficult to fully wet and fill these micro interfaces during the second-level curing process, resulting in interface bonding mainly relying on physical adsorption. After humid heat aging, they fail due to hydrolysis or stress accumulation.
[0005] In existing technologies, there is a defect of insufficient adhesion between the insulating adhesive and the back of the battery after aging. Specifically, after the double 85 aging test (85℃ / 85%RH) or thermal cycling aging, the insulating adhesive layer delaminates at the interface with the battery cell, causing insulation failure between the positive and negative electrodes of the module, which in turn leads to a short circuit and seriously affects the long-term reliability and power generation efficiency of the photovoltaic module.
[0006] Therefore, how to provide an insulating adhesive with stronger adhesion in back contact batteries and its preparation method has become an urgent problem to be solved. Summary of the Invention
[0007] To address the aforementioned technical problems, this application aims to provide an insulating adhesive, a photovoltaic module, and a method for preparing the same. The insulating adhesive described in this application can significantly improve its adhesion to the back of the solar cell after aging. After undergoing a double 85 aging test (85℃ / 85%RH) or thermal cycling aging, no delamination occurs between the insulating adhesive layer and the solar cell interface, thereby improving the long-term reliability and power generation efficiency of the photovoltaic module.
[0008] To achieve this objective, the following technical solution is adopted in this application:
[0009] In a first aspect, this application provides an insulating adhesive, the raw materials for which include a main resin, an active diluent, a thermosetting functional monomer, an adhesion promoter, an inorganic filler, a photoinitiator, a silane coupling agent, and additives; the main resin includes a block copolymer and / or a high- and low-Tg resin blend system; the high- and low-Tg resin blend system includes a high-Tg resin and a low-Tg resin.
[0010] The insulating adhesive provided in this application uses a block copolymer and / or high- and low-Tg resin blend system as the main resin. This material exhibits lower shrinkage during curing, overcoming the warping problem caused by high curing shrinkage (1%-5%) and increased stress in traditional epoxy insulating adhesives under filler-free or low-filler conditions. Furthermore, the high-Tg resin in this application provides sufficient cohesive strength and thixotropy at room temperature, supporting high-precision screen printing, while the low-Tg resin enables stress relaxation and enhanced interfacial adhesion under high-temperature lamination, further improving interfacial adhesion. During the curing process of the block copolymer, hard segments (such as polystyrene segments) and soft segments (such as polybutadiene segments) undergo microphase separation. The hard segment regions provide strength as physical crosslinking points, while the soft segment regions absorb and disperse stress, inhibiting the accumulation of shrinkage stress at the molecular level. In the high- and low-Tg blend system, the high-Tg resin is rich in acrylate double bonds and forms a rigid network through free radical chain polymerization under UV irradiation; the low-Tg polyester resin does not participate in UV curing and is uniformly distributed in the rigid network as a flexible dispersed phase. Under high lamination temperatures, the low-Tg phase softens and flows, filling the microscopic irregularities of the interface, while simultaneously dissipating curing shrinkage stress through molecular chain segment movement. These two processes work synergistically to achieve a balance of rigidity and flexibility in mechanical properties.
[0011] The reactive diluent in this application can reduce the viscosity of the system to improve printability and regulate the curing speed; the thermosetting functional monomer remains inert and unreacted during the UV curing stage, and remains stable and undecapsulated under the thermal shock of the stringing process (150℃-180℃ / 3-5 seconds), while it decapsulates at the lamination temperature and releases -NCO groups, which can form strong covalent bonds with hydroxyl groups (-OH) to improve the adhesion of the interface; the adhesion promoter forms strong coordination bonds with the inorganic surface of the battery cell through its phosphate ester groups, directly improving the interfacial adhesion; the inorganic filler is used to improve the thixotropy of the ink to facilitate precision printing, and its nanoparticles can form physical anchoring points to enhance the strength of the cured product; the photoinitiator is used to efficiently initiate the UV free radical polymerization reaction; the silane coupling agent further enhances the bonding force between the organic adhesive layer and the inorganic battery cell interface; the additives are used to improve the surface leveling of the adhesive layer and eliminate bubbles generated during mixing and printing.
[0012] Tg (glass transition temperature) is the critical temperature at which a polymer material transitions from a glassy state to a highly elastic state (or viscous flow state). In this application, "high Tg resin" refers to resin with Tg ≥ 40℃, and "low Tg resin" refers to resin with Tg ≤ 15℃.
[0013] The following are preferred technical solutions of this application, but are not intended to limit the technical solutions provided in this application. Through the following preferred technical solutions, the technical objectives and beneficial effects of this application can be better achieved.
[0014] In some embodiments, the high Tg resin comprises any one or a combination of at least two of dipentaerythritol pentaacrylate, trimethylolpropane triacrylate, or pentaerythritol tetraacrylate. Typical but non-limiting combinations include combinations of dipentaerythritol pentaacrylate and trimethylolpropane triacrylate, combinations of trimethylolpropane triacrylate and pentaerythritol tetraacrylate, combinations of dipentaerythritol pentaacrylate and pentaerythritol tetraacrylate, and combinations of dipentaerythritol pentaacrylate, trimethylolpropane triacrylate, and pentaerythritol tetraacrylate.
[0015] In some embodiments, the low Tg resin comprises any one or a combination of at least two of polyethylene adipate diol, polycaprolactone diol, or polycarbonate diol. Typical but non-limiting combinations include combinations of polyethylene adipate diol and polycaprolactone diol, combinations of polycaprolactone diol and polycarbonate diol, combinations of polyethylene adipate diol and polycarbonate diol, and combinations of polyethylene adipate diol, polycaprolactone diol, and polycarbonate diol.
[0016] In some embodiments, the mass ratio of the high-Tg resin to the low-Tg resin is 1:(0.8-1.2), for example, it can be 1:0.8, 1:0.85, 1:0.9, 1:0.95, 1:1.0, 1:1.1 or 1:1.2, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0017] This application further controls the mass ratio of high-Tg resin to low-Tg resin to be 1:(0.8-1.2). This mass ratio affects the microscopic phase continuity and stress transfer efficiency of the blend system: If the high-Tg resin content is too high (mass ratio > 1:0.8, i.e., the high-Tg proportion is too high), the system becomes too rigid, and the low-Tg resin cannot form a continuous or sufficiently large flexible dispersed phase. This results in insufficient stress relaxation under high lamination temperatures, difficulty in releasing curing shrinkage stress, and a tendency for cell warping. Furthermore, the adhesive layer exhibits poor toughness and reduced crack resistance after aging. If the high-Tg resin content is too low (mass ratio < 1:1.2, i.e., the low-Tg proportion is too high), the overall cohesive strength of the system is insufficient, thixotropy deteriorates, and sagging or edge expansion easily occurs during screen printing, affecting printing accuracy. Simultaneously, the initial peel strength is too low, failing to meet the production line's requirements for the adhesive layer's resistance to disturbance after setting. This application achieves a dual continuous or well-dispersed structure of rigid network and flexible dispersed phase by controlling the mass ratio of the two phases within the range of 1:(0.8-1.2), thus taking into account printability, initial strength and adhesion retention after aging.
[0018] In some embodiments, based on the total mass of the raw materials for preparing the insulating adhesive being 100 wt%, the main resin accounts for 40.0 wt% to 80.0 wt%, for example, it can be 40.0 wt%, 45.0 wt%, 50.0 wt%, 55.0 wt%, 60.0 wt%, 65.0 wt%, 70.0 wt%, 75.0 wt%, or 80.0 wt%, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0019] In some embodiments, based on a total mass of 100wt% of the raw materials for preparing the insulating adhesive, the reactive diluent accounts for 5.0wt%-15.0wt%, for example, it can be 5.0wt%, 6.0wt%, 7.0wt%, 8.0wt%, 9.0wt%, 10.0wt%, 11.0wt%, 12.0wt%, 13.0wt%, 14.0wt%, or 15.0wt%, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0020] In some embodiments, based on the total mass of the raw materials for preparing the insulating adhesive being 100 wt%, the thermosetting functional monomer accounts for 5.0 wt% to 15.0 wt%, for example, it can be 5.0 wt%, 6.0 wt%, 7.0 wt%, 8.0 wt%, 9.0 wt%, 10.0 wt%, 11.0 wt%, 12.0 wt%, 13.0 wt%, 14.0 wt%, or 15.0 wt%, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0021] In some embodiments, based on a total mass of 100wt% of the raw materials used to prepare the insulating adhesive, the adhesion promoter accounts for 3.0wt%-8.0wt%, for example, it can be 3.0wt%, 3.5wt%, 4.0wt%, 4.5wt%, 5.0wt%, 5.5wt%, 6.0wt%, 6.5wt%, 7.0wt%, 7.5wt%, or 8.0wt%, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0022] In some embodiments, based on a total mass of 100wt% of the raw materials used to prepare the insulating adhesive, the inorganic filler accounts for 2.0wt%-6.0wt%, for example, it can be 2.0wt%, 2.5wt%, 3.0wt%, 3.5wt%, 4.0wt%, 4.5wt%, 5.0wt%, 5.5wt%, or 6.0wt%, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0023] In some embodiments, based on the total mass of the raw materials for preparing the insulating adhesive being 100 wt%, the photoinitiator accounts for 1.0 wt% to 4.0 wt%, for example, it can be 1.0 wt%, 1.5 wt%, 2.0 wt%, 2.5 wt%, 3.0 wt%, 3.5 wt%, or 4.0 wt%, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0024] In some embodiments, based on the total mass of the raw materials for preparing the insulating adhesive being 100 wt%, the silane coupling agent accounts for 0.5 wt% to 2.0 wt%, for example, it can be 0.5 wt%, 0.8 wt%, 1.0 wt%, 1.2 wt%, 1.5 wt%, 1.8 wt%, or 2.0 wt%, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0025] In some embodiments, based on the total mass of the raw materials for preparing the insulating adhesive being 100wt%, the additives account for 0.5wt%-2.0wt%, for example, 0.5wt%, 0.8wt%, 1.0wt%, 1.2wt%, 1.5wt%, 1.8wt%, or 2.0wt%, but are not limited to the listed values; other unlisted values within the range are also applicable.
[0026] In some embodiments, the block copolymer includes any one or a combination of at least two of polystyrene-block-polybutadiene-block-polystyrene (SBS), polystyrene-block-polyisoprene-block-polystyrene (SIS), polystyrene-block-poly(ethylene-butene)-block-polystyrene (SEBS), polystyrene-block-poly(ethylene-propylene)-block-polystyrene (SEPS), or polyurethane-block-polyether copolymers; typical but non-limiting combinations include polystyrene-block-polybutadiene-block-polyether copolymers. Combinations of polystyrene-block-polyisoprene-block-polystyrene (SIS), combinations of polystyrene-block-polybutadiene-block-polystyrene (SBS) and polystyrene-block-poly(ethylene-butene)-block-polystyrene (SEBS), combinations of polystyrene-block-polybutadiene-block-polystyrene (SBS) and polystyrene-block-poly(ethylene-propylene)-block-polystyrene (SEPS), preferably polystyrene-block-polybutadiene-block-polystyrene (SBS).
[0027] In some embodiments, the reactive diluent includes isobornyl acrylate (IBOA).
[0028] In some embodiments, the thermosetting functional monomer comprises a blocked isocyanate with a desealing temperature >180°C.
[0029] In some embodiments, the adhesion promoter includes polyethylene glycol monomethacrylate phosphate.
[0030] In some embodiments, the inorganic filler comprises hydrophobic fumed silica.
[0031] The role of "hydrophobic fumed silica" in this application is as follows: Insulating adhesives used in photovoltaic modules are exposed to a humid and hot environment (dual 85 test) for extended periods. If hydrophilic fumed silica is used, its surface's numerous silanol groups will absorb moisture, leading to hydrolysis of the adhesive layer and decreased interfacial adhesion during aging. Hydrophobic fumed silica (such as that surface-treated with dimethyldichlorosilane or hexamethyldisilazane) has a surface covered with non-polar groups, significantly reducing hygroscopicity while still providing excellent thixotropy and anti-settling effects, ensuring screen printing accuracy.
[0032] In some embodiments, the photoinitiator comprises 2,4,6-trimethylbenzoyldiphenylphosphine oxide (TPO).
[0033] In some embodiments, the silane coupling agent includes KH-570 and / or aminosilane.
[0034] In some embodiments, the additives include isophorone leveling agents and / or fatty acid ester defoamers.
[0035] Secondly, this application provides a method for preparing the insulating adhesive as described in the first aspect, the method comprising the following steps:
[0036] The raw materials for preparing the insulating adhesive described in the first aspect are first subjected to UV pre-curing to obtain an intermediate state of the insulating adhesive; the intermediate state of the insulating adhesive is then subjected to lamination and thermo-curing to obtain the insulating adhesive; the degree of curing of the intermediate state of the insulating adhesive is 60%-70%.
[0037] The method for preparing the insulating adhesive provided in this application adopts a staged curing strategy of "UV pre-curing + lamination thermal curing". While ensuring the curing speed (UV curing speed is faster), it can achieve low stress while avoiding excessive filler, avoid warping caused by shrinkage stress, and ensure that the insulating adhesive and the support interface can be fully wetted, avoiding delamination caused by moisture accumulation after subsequent aging.
[0038] On the one hand, UV pre-curing meets the process requirements, achieving surface drying and shaping of the adhesive layer, completing only about 60%-70% of the curing degree. The UV pre-curing stage is sufficient to resist production line disturbances, but it deliberately retains the activity of most of the thermosetting components to avoid premature reaction, and at the same time, it is conducive to releasing the curing shrinkage stress generated in the early stage.
[0039] On the other hand, lamination thermosetting is key to achieving high adhesion. High temperatures cause the thermosetting functional monomers to completely deseal, and the released -NCO groups can react with -OH groups on the support interface surface to generate a large number of covalent bonds, achieving chemical bonding. At the same time, the low Tg resin in the adhesive layer softens, stress relaxes, and interface adhesion is enhanced, ensuring that the insulating adhesive completes final and complete curing under low stress.
[0040] This application first uses UV pre-curing to initially shape the adhesive layer while retaining a window for subsequent reactions. The lamination and thermosetting process possesses excellent interfacial compliance and stress relaxation capabilities, which, combined with the thermosetting reaction, achieves chemical bonding under low stress. Ultimately, it achieves the dual advantages of "rapid UV shaping + thorough thermosetting wetting," significantly improving adhesion after aging while ensuring production efficiency.
[0041] This application controls the degree of curing of the intermediate state of the insulating adhesive to be 60%-70%, for example, it can be 60%, 62%, 65%, 68% or 70%, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0042] If the intermediate state of the insulating adhesive is too well cured, the UV curing stage will consume too many acrylate double bonds, resulting in an excessively high crosslinking network density, fewer residual unreacted functional groups, and an overly rigid network that restricts the mobility of the adhesive molecular chains during lamination. This makes it difficult for the thermosetting functional monomers to fully unpack and migrate to the interface, reducing chemical bonding. Additionally, the shrinkage stress generated cannot be released subsequently. If the intermediate state of the insulating adhesive is too poorly cured, the adhesive layer will not be sufficiently dry and will lack mechanical strength. This can easily lead to the adhesive layer being pulled, displaced, or contaminating the solder ribbon during photovoltaic bonding. Furthermore, excessive liquid components may overflow under the high temperature and pressure of lamination, contaminating other areas of the solar cell or affecting the encapsulation effect.
[0043] The degree of cure in this application can be monitored by Fourier transform infrared spectroscopy (FTIR) at 810 cm⁻¹. -1 Calculate the conversion rate by analyzing the attenuation of the peak area of the characteristic peak.
[0044] In some embodiments, the wavelength of the UV light used for UV pre-curing is 365nm-395nm, for example, it can be 365nm, 375nm, 385nm or 395nm, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0045] In some embodiments, the irradiation energy density during the UV pre-curing process is 400 mJ / cm². 2 -800mJ / cm 2 For example, it could be 400mJ / cm 2 450mJ / cm 2 500mJ / cm 2 550mJ / cm 2 600mJ / cm 2 650mJ / cm 2 700mJ / cm 2 750mJ / cm 2 Or 800mJ / cm 2 However, this does not limit the listed values; other unlisted values within the range are also applicable.
[0046] This application achieves this by further controlling the irradiation energy density during the UV pre-curing process to 400 mJ / cm². 2 -800mJ / cm 2The irradiation energy density during UV pre-curing affects the decomposition efficiency of the photoinitiator and the rate of free radical generation. If the irradiation energy density during UV pre-curing is too high, the photoinitiator will decompose excessively, generating an excessive amount of free radicals in a short time. This leads to an excessively high conversion rate of the C=C double bonds in the acrylate, and the degree of curing in the intermediate state of the insulating adhesive may exceed 70% or even reach over 80%. At this point, the adhesive layer has formed a highly cross-linked rigid network. On the one hand, a large amount of shrinkage stress is generated during the UV stage and cannot be released subsequently, increasing the risk of cell warping. On the other hand, the high cross-linking density restricts the mobility of the adhesive layer molecular chains under lamination high temperatures. The thermosetting functional monomers (blocked isocyanates) are physically confined in the dense cross-linked network, making it difficult for them to fully migrate to the cell interface and react with -OH groups, resulting in a decrease in chemical bond density. Meanwhile, premature consumption of excessive reactive functional groups reduces the number of active sites available for further crosslinking during the lamination stage, resulting in insufficient covalent bonds between the insulating adhesive and the interface. This ultimately leads to a decrease in peel strength and retention rate after aging. If the irradiation energy density during UV pre-curing is too low, the photoinitiator will not decompose sufficiently, the free radical concentration in the system will be too low, and a large number of acrylate C=C double bonds will fail to participate in the polymerization reaction. The degree of curing in the intermediate state of the insulating adhesive may only be 40%-50%, failing to meet the minimum requirement of 60%. At this point, the surface drying effect of the adhesive layer is insufficient, and the cohesive strength is extremely low. During the subsequent photovoltaic ribbon setting process, the insulating adhesive layer is easily disturbed, deformed, stringed, or even detached, seriously affecting the production line yield and ribbon positioning accuracy. At the same time, the excessively low degree of curing means that the adhesive layer still contains a large number of unreacted low molecular weight components (such as reactive diluents, unpolymerized monomers, etc.). These liquid components are prone to overflow under the high temperature and pressure of lamination, contaminating the surface of the solar cell or affecting the adhesion of the encapsulation film. In addition, although more thermosetting functional monomers are retained, the adhesive layer may flow uncontrollably during lamination because the UV stage does not form a sufficient network skeleton to fix the shape of the adhesive layer, resulting in uneven distribution of the insulating adhesive and loss of design accuracy.
[0047] In some embodiments, the lamination thermosetting includes a first-stage thermosetting and a second-stage thermosetting;
[0048] In some embodiments, the pressure during the lamination thermosetting process is 10 kPa-70 kPa, for example, it can be 10 kPa, 20 kPa, 30 kPa, 40 kPa, 60 kPa or 70 kPa, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0049] In some embodiments, the temperature for the first stage of thermosetting is 90°C-120°C, for example, it can be 90°C, 95°C, 100°C, 105°C, 110°C, 115°C or 120°C, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0050] In some embodiments, the time for the first stage of thermal curing is 3-6 minutes, for example, 3 minutes, 4 minutes, 5 minutes or 6 minutes, but not limited to the listed values. Other unlisted values within the range are also applicable.
[0051] In some embodiments, the temperature for the second stage of thermosetting is 130°C-150°C, for example, 130°C, 135°C, 140°C, 145°C or 150°C, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0052] This application further controls the lamination thermosetting process by dividing it into two stages of heating, controlling the temperature of the first stage thermosetting at 90℃-120℃ and the second stage at 130℃-150℃. The different thermosetting temperatures affect the desealing rate and extent of the blocked isocyanate, the melt flow behavior of the encapsulating film, the softening and stress relaxation effect of the low Tg resin in the insulating adhesive, and the progress and efficiency of the chemical bonding reaction at the interface. If the temperature of the first stage thermosetting is too high, a large amount of desealing of the blocked isocyanate and the cross-linking reaction of -NCO will be prematurely triggered in the first stage. At this time, the encapsulating film (such as EVA / POE) has just begun to melt and has not yet flowed sufficiently under pressure to expel interlayer bubbles, and the insulating adhesive layer has not completed sufficient wetting of the micro-uneven structure on the back of the battery cell at a lower temperature. The chemical bonding reaction proceeds prematurely under the condition of "insufficient interfacial contact and incomplete wetting", resulting in a large number of -NCO groups reacting with hydroxyl groups in the interior of the adhesive layer or in local areas of the interface, rather than being uniformly distributed throughout the entire interface, resulting in a low effective chemical bonding density. Meanwhile, premature thermosetting reactions generate new shrinkage stresses, while the stresses already generated during the UV pre-curing stage have not yet been released through the softening effect of the low-Tg resin. The superposition of these two stresses exacerbates interfacial stress concentration, making interfacial delamination more likely during subsequent aging. Furthermore, excessively high temperatures in the first stage accelerate the pre-crosslinking or thermal oxidation side reactions of the encapsulating film, affecting its fluidity and final encapsulation effect. If the thermosetting temperature in the second stage is too high, although the desealing rate of the isocyanate will be significantly accelerated, the excessively high temperature will bring a series of negative effects. First, the main resins, such as polyester resin and polyester acrylate, may undergo thermal oxidation degradation at 200℃, resulting in molecular chain breakage and a significant decrease in the cohesive strength of the adhesive layer, leading to deterioration of the bulk mechanical properties. Second, excessively high lamination temperatures will cause the encapsulating film (especially EVA) to decompose, generating a large amount of volatile gases (such as acetic acid and hydrocarbons). If these bubbles are not expelled in time, they will remain at the interface between the insulating adhesive and the battery cell, forming voids and significantly reducing the effective contact area and adhesion. Secondly, the partially cross-linked network formed in the first stage may shrink excessively or become brittle under the ultra-high temperature in the second stage. Even if the flexible chain segments of the low Tg resin soften, they cannot effectively dissipate stress because the cross-linking density of the entire system is too high and the movement of molecular chains is restricted. Ultimately, this results in a hard and brittle adhesive layer after curing, and the peel strength retention rate drops sharply after aging.
[0053] In some embodiments, the second stage of thermosetting time is 5 min to 10 min, for example, 5 min, 6 min, 7 min, 8 min, 9 min or 10 min, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0054] Thirdly, this application provides a photovoltaic module, which includes the insulating adhesive described in the first aspect or the insulating adhesive prepared by the preparation method described in the second aspect.
[0055] Fourthly, this application provides a method for preparing a photovoltaic module as described in the first aspect, the method comprising the following steps:
[0056] (1) Plasma cleaning of BC solar cells;
[0057] (2) The raw materials for preparing the insulating adhesive described in the first aspect are placed on the back side of the cleaned BC battery cell;
[0058] (3) UV pre-curing of the raw materials for preparing the insulating adhesive to obtain an intermediate state of insulating adhesive with a curing degree of 60%-70%, and then setting photovoltaic welding ribbons to obtain BC cell strings;
[0059] (4) The BC battery string is encapsulated and then laminated and thermocured to obtain the photovoltaic module.
[0060] The integrated solution of "plasma activation pretreatment + UV pre-curing + lamination thermal curing" provided in this application significantly improves the adhesion between the insulating adhesive layer and the back of the solar cell after aging. After undergoing double 85 aging test (85℃ / 85%RH) or thermal cycling aging, no delamination occurred between the insulating adhesive layer and the solar cell interface, thus improving the long-term reliability and power generation efficiency of the photovoltaic module.
[0061] Organic contaminants (such as fingerprints, residual flux, and rust-preventive oil) are often present on the back of BC solar cells. These contaminants are unavoidable during cell fabrication, handling, and storage. These organic materials have extremely low surface energy (below approximately 30 dynes), forming a weak interface layer that hinders direct contact between the insulating adhesive and the inorganic substrate.
[0062] The ion cleaning method described in this application can thoroughly remove organic contaminants from the surface within tens of seconds through the dual action of physical bombardment (Ar+ ion sputtering) and chemical reaction (O2 free radical oxidative decomposition). At the same time, it introduces highly active functional groups such as -OH and -NH2 into the cleaned inorganic surface, increasing the surface energy from about 35 dynes to more than 60 dynes. The -OH introduced on the surface provides ideal chemical bonding reaction sites for subsequent thermosetting functional monomers (such as blocked isocyanates) (-NCO+-OH→-NH-COO-), realizing a fundamental transformation from "physical adsorption + contaminant mediation" to "direct contact + covalent bonding".
[0063] This application does not impose any special limitations on the methods of "setting photovoltaic solder strips" and "encapsulating BC battery strings". Both "setting photovoltaic solder strips" and "encapsulating BC battery strings" are completed using conventional methods in the prior art, as long as the corresponding effects can be achieved.
[0064] It should be noted that the traditional welding temperature is controlled at 150℃-180℃ for 3-5 seconds. At this temperature, the thermosetting functional monomers can remain stable and unsealed under short-term thermal shock. Although this is insufficient to trigger a large-scale thermosetting reaction, it allows the adhesive layer to be initially heated and removes trace amounts of moisture adsorbed at the interface, creating a clean interface for full chemical bonding in subsequent lamination processes.
[0065] In some embodiments, the plasma cleaning uses an argon-oxygen mixture.
[0066] In some embodiments, the volume ratio of argon to oxygen in the argon-oxygen mixture is (90-95):(5-10), for example, it can be 90:10, 92:8 or 95:5, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0067] In some embodiments, the vacuum degree of the plasma cleaning is 10Pa-20Pa, for example, it can be 10Pa, 15Pa, 18Pa or 20Pa, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0068] In some embodiments, the power of the plasma cleaning is 150W-250W, for example, it can be 150W, 180W, 200W, 220W or 250W, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0069] In some embodiments, the plasma cleaning time is 45s-90s, for example, it can be 45s, 50s, 60s, 70s, 80s or 90s, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0070] As a preferred embodiment of the preparation method described in this application, the preparation method includes the following steps:
[0071] (1) BC cells were plasma cleaned for 45s-90s under the conditions of argon and oxygen volume ratio of (90-95):(5-10), vacuum degree of 10Pa-20Pa, and power of 150W-250W.
[0072] (2) The raw materials for preparing the insulating adhesive described in the first aspect are placed on the back of the cleaned BC battery cell using a 300-360 mesh screen, with the squeegee pressure set to 70N-85N and the printing speed set to 150mm / s-250mm / s.
[0073] (3) Use wavelengths of 365nm-395nm and irradiation energy density of 400mJ / cm². 2 -800mJ / cm 2 UV light is used to pre-cur the raw materials for preparing the insulating adhesive to obtain an intermediate state of insulating adhesive with a curing degree of 60%-70%. Then, photovoltaic ribbons are set to obtain BC cell strings.
[0074] (4) The BC battery string is encapsulated, and then thermally cured in the first stage for 3 min-6 min under the conditions of 10KPa-70KPa and 90℃-120℃, and then thermally cured in the second stage for 5 min-10 min at 130℃-150℃ to complete the lamination thermal curing and obtain the photovoltaic module.
[0075] The numerical range described in this application includes not only the point values listed above, but also any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of brevity, this application will not exhaustively list the specific point values included in the range.
[0076] Compared with the prior art, this application has at least the following beneficial effects:
[0077] (1) The insulating adhesive provided in this application uses a block copolymer and / or a blend of high and low Tg resins as the main resin. This material has a lower shrinkage rate during curing, which overcomes the warping problem caused by high curing shrinkage (1%-5%) and increased stress in traditional epoxy insulating adhesives under filler-free or low-filler conditions. In addition, the high Tg resin in this application provides sufficient cohesive strength and thixotropy at room temperature, supporting high-precision screen printing, while the low Tg resin can achieve stress relaxation and enhanced interfacial bonding under high lamination temperature, further improving the adhesion of the interface.
[0078] (2) The method for preparing the insulating adhesive provided in this application adopts a staged curing strategy of "UV pre-curing + lamination heat curing". While ensuring the curing speed (UV curing speed is faster), it can achieve low stress while avoiding excessive filler, avoid warping caused by shrinkage stress, and ensure that the insulating adhesive and the support interface can be fully wetted, thus avoiding delamination caused by moisture accumulation after subsequent aging.
[0079] (3) In this application, the ion cleaning can completely remove organic pollutants on the surface within tens of seconds through the dual action of physical bombardment (Ar+ ion sputtering) and chemical reaction (O2 free radical oxidation decomposition). At the same time, it introduces highly active functional groups such as -OH and -NH2 into the cleaned inorganic surface, increasing the surface energy from about 35 dynes to more than 60 dynes. The -OH introduced on the surface provides an ideal chemical bonding reaction site for subsequent thermosetting functional monomers (such as blocked isocyanates) (-NCO+-OH→-NH-COO-), realizing a fundamental transformation from "physical adsorption + pollutant mediation" to "direct contact + covalent bonding". Detailed Implementation
[0080] The technical solution of this application will be further described below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely to help understand this application and should not be regarded as specific limitations on this application.
[0081] The scope of this application can be defined by lower and upper limits. The selected lower and upper limits define the boundaries of a specific range. The range defined in this way can be defined by the inclusion or exclusion of endpoints. Any endpoint can be independently selected for inclusion or exclusion, and all lower and upper limits can be arbitrarily combined to form new ranges. That is, any lower limit can be combined with any upper limit to form a valid range. For example, if the ranges of 60~120 and 80~110 are listed for specific parameters, it should be understood that the ranges of 60~110 and 80~120 also fall within the scope of this application. In addition, if the minimum range values 1 and 2 are listed, and the maximum range values 3, 4 and 5 are also listed, then all ranges of 1~3, 1~4, 1~5, 2~3, 2~4 and 2~5 fall within the scope of this application. In this application, the numerical range "a~b" represents a shortened representation of any combination of real numbers between a and b, where a and b are both real numbers. For example, the numerical range "0~5" means that all real numbers between 0 and 5 have been fully listed in this document, and "0~5" is only a shortened representation of this set of numerical combinations. When a parameter is expressed as an integer ≥2, it is equivalent to listing positive integers that meet the requirements, such as 2, 3, 4, 5, 6, 7, 8, 9, 10, etc. When a parameter is expressed as an integer selected from "2~10", it is equivalent to listing any integer among 2, 3, 4, 5, 6, 7, 8, 9, and 10.
[0082] In this application, "at least two combinations" refers to a quantity greater than or equal to 2 unless otherwise specified. For example, "any one or at least two combinations" means any one of the listed items can be selected, or a combination of at least two of the listed items formed in a manner that does not conflict and enables the implementation of this application. In this application, unless otherwise specified, the features or solutions corresponding to "and / or" cover any one of two or more related listed items, as well as any and all combinations of the related listed items. The arbitrary and all combinations include any two related listed items, any more related listed items, or a combination of all related listed items. For example, "A and / or B" means a set consisting of A, B, and combinations of A and B, where "containing A and / or B" can be understood, depending on the context of the statement, as containing A, containing B, or simultaneously containing both A and B. In this application, "optional" means that the corresponding feature, component, step or solution is not necessary, that is, it is selected from either "with" or "without". If there are multiple "optional" limitations in a technical solution, unless otherwise specified and there is no technical conflict or mutual constraint, each "optional" limitation is independent and does not affect the others.
[0083] In this application, technical features or solutions described using open-ended terms such as "comprising" or "including" do not exclude additional non-conflicting elements beyond those listed unless otherwise specified. They are considered to disclose both closed-ended features or solutions consisting solely of the listed elements and open-ended features or solutions that may include additional non-conflicting elements beyond the listed elements. For example, if A includes a1, a2, and a3, unless otherwise specified, this means that A can consist only of a1, a2, and a3, or it can include other non-conflicting elements based on a1, a2, and a3. This corresponds to the disclosure of technical solutions such as "A consists of a1, a2, and a3," "A is selected from a1, a2, and a3," and "A not only includes a1, a2, and a3, but may also include other non-conflicting elements." All embodiments and optional embodiments of this application, unless otherwise specified and without technical conflict, can be combined to form new technical solutions, and such combinations fall within the scope of this application. The term "embodiment" as used in this application means that a specific feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment or implementation of this application. The appearance of this phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment mutually exclusive with other embodiments. Those skilled in the art can explicitly and implicitly understand that the embodiments described in this application can be combined with other embodiments that do not conflict with existing technologies. The ordinal numbers "first," "second," "third," and "fourth," etc., used in this application in the expressions "first aspect," "second aspect," "third aspect," and "fourth aspect," are for descriptive purposes only and should not be construed as indicating or implying relative importance or quantity, nor should they be construed as implicitly specifying the importance or quantity of the indicated technical features. They serve only as a non-exhaustive enumeration and do not constitute a closed limitation on quantity.
[0084] In this application, the order in which the steps are written in the methods described in the various embodiments does not imply a strict execution order. The actual execution order of each step should be determined according to its function and possible internal logic. Unless otherwise specified, all steps in this application can be executed in the order they are written, or in any order without technical conflict. For example, if the method includes steps (a) and (b), it means that the method may include steps (a) and (b) executed sequentially, or it may include steps (b) and (a) executed sequentially. If the method also includes step (c), then step (c) can be added to the method in any order without conflict, including but not limited to the execution order of steps (a), (b), and (c), steps (a), (c), and (b), steps (c), (a), and (b), etc.
[0085] Unless otherwise specified, all reagents and consumables used in the following examples and comparative examples were purchased from conventional reagent manufacturers in the art; unless otherwise specified, the experimental methods and techniques used were conventional methods and techniques in the art.
[0086] Example 1
[0087] This embodiment provides an insulating adhesive. Based on a total mass of 100 wt% of the raw materials used in preparing the insulating adhesive, the raw materials include 67.0 wt% of dipentaerythritol pentaacrylate (Tg 40℃-60℃) and polyethylene adipate diol (Tg 10℃~0℃) in a 1:1 mass ratio as the main resin, 10.0 wt% of isobornyl acrylate as an reactive diluent, and 10.0 wt% of blocked isocyanate (Asahi Kasei's Duranat) with a thermosetting functional monomer deblocking temperature >180℃. MF-K60X hexamethylene diisocyanate (HDI) is a blocked isocyanate, 5.0 wt% adhesion promoter polyethylene glycol monomethacrylate phosphate, 4.0 wt% inorganic filler hydrophobic fumed silica, 2.0 wt% photoinitiator TPO, 1.0 wt% silane coupling agent KH-570, and 1.0 wt% isophorone leveling agent and fatty acid ester defoamer (SN-DEFOAMER JK, Japan Seinopco) in a 1:1 mass ratio.
[0088] Example 2
[0089] This embodiment provides an insulating adhesive. Based on a total mass of 100 wt% of the raw materials used in preparing the insulating adhesive, the raw materials include 75.5 wt% of a 1:1 mixture of dipentaerythritol pentaacrylate (Tg 40℃-60℃) and polyethylene adipate diol (Tg 10℃~0℃) as the main resin; 8.0 wt% of isobornyl acrylate as an reactive diluent; 8.0 wt% of a thermosetting functional monomer with a deblocking temperature >180℃ (Asahi Kasei's Durnate MF-K60X hexamethylene diisocyanate (HDI) type blocked isocyanate); 3.0 wt% of polyethylene glycol monomethacrylate phosphate as an adhesion promoter; 2.5 wt% of hydrophobic fumed silica as an inorganic filler; 1.5 wt% of TPO as a photoinitiator; and 1.0 wt% of aminosilane as a silane coupling agent (Shin-Etsu Chemical's KBM-903). —3-Aminopropyltrimethoxysilane) and 0.5wt% isophorone leveling agent and fatty acid ester defoamer (SN-DEFOAMER JK, Japan Seinnopco) in a mass ratio of 1:1.
[0090] Example 3
[0091] This embodiment provides an insulating adhesive. Based on a total mass of 100 wt% of the raw materials used in preparing the insulating adhesive, the raw materials include 55.0 wt% of SEBS (polystyrene-block-poly(ethylene-butene)-block-polystyrene as the main resin), 15.0 wt% of isoborneol acrylate as an active diluent, 13.0 wt% of blocked isocyanate (Asahi Kasei's Durnate MF-K60X hexamethylene diisocyanate (HDI) series blocked isocyanate) with a thermosetting functional monomer deblocking temperature >180°C, 5.0 wt% of polyethylene glycol monomethacrylate phosphate as an adhesion promoter, 5.0 wt% of hydrophobic fumed silica as an inorganic filler, 3.0 wt% of TPO as a photoinitiator, 2.0 wt% of KH-570 as a silane coupling agent, and 2.0 wt% of isophorone leveling agent and fatty acid ester defoamer (SN-DEFOAMER JK, Seinopco, Japan) at a mass ratio of 1:1.2.
[0092] Example 4
[0093] This embodiment provides an insulating adhesive, which differs from Embodiment 1 only in that the mass ratio of dipentaerythritol pentaacrylate and polyethylene adipate diol is 1:0.5, while the mass fraction of the remaining components remains unchanged.
[0094] Example 5
[0095] This embodiment provides an insulating adhesive, which differs from Embodiment 1 only in that the mass ratio of dipentaerythritol pentaacrylate and polyethylene adipate diol is 1:2, while the mass fraction of the remaining components remains unchanged.
[0096] Comparative Example 1
[0097] This comparative example provides an insulating adhesive, which differs from Example 1 only in that polyethylene adipate diol is replaced with an equal mass of dipentaerythritol pentaacrylate, i.e., it contains only high Tg resin and no low Tg resin, while the other components remain unchanged.
[0098] Application Example 1
[0099] This application example provides a photovoltaic module, which includes the insulating adhesive described in Example 1;
[0100] The photovoltaic module manufacturing method provided in this embodiment includes the following steps:
[0101] (1) The BC cell was plasma cleaned for 70s under the conditions of argon and oxygen volume ratio of 95:5, vacuum degree of 15Pa and power of 200W.
[0102] (2) The raw materials for preparing the insulating adhesive described in Example 1 were screen-printed on the back of the cleaned BC battery cell using a 350-mesh screen, with a squeegee pressure of 80N and a printing speed of 200mm / s.
[0103] (3) Use a wavelength of 395nm and an irradiation energy density of 600mJ / cm². 2 UV light is used to pre-cur the raw materials for preparing the insulating adhesive to obtain an intermediate state of insulating adhesive with a curing degree of 65%. Then, photovoltaic ribbons are set to obtain BC cell strings.
[0104] (4) The BC battery string is encapsulated, and then heat-cured for 5 minutes in the first stage at 60KPa and 100℃, and then heat-cured for 8 minutes in the second stage at 145℃ to complete the lamination heat curing and obtain the photovoltaic module.
[0105] Application Examples 2-5
[0106] Application Examples 2-5 each provide a photovoltaic module. The difference between the preparation method of the photovoltaic module and Application Example 1 is that the raw materials for preparing the insulating adhesive used in step (2) of Example 1 are replaced with the raw materials for preparing the insulating adhesive of Examples 2-5, and the rest of the preparation method remains unchanged.
[0107] Application Example 6
[0108] This application example provides a photovoltaic module, which differs from Application Example 1 only in that, during the fabrication of this photovoltaic module, the UV light irradiation energy density in step (3) is adjusted to 300 mJ / cm². 2 The actual degree of curing is about 48%, and the remaining steps remain unchanged.
[0109] Application Example 7
[0110] This application example provides a photovoltaic module, which differs from Application Example 1 only in that, during the fabrication of this photovoltaic module, the UV light irradiation energy density in step (3) is adjusted to 900 mJ / cm². 2 The actual degree of curing is about 80%, and the remaining steps remain unchanged.
[0111] Application Example 8
[0112] This application example provides a photovoltaic module. The only difference from application example 1 is that when preparing the photovoltaic module, the temperature of the first stage of thermal curing in step (4) is replaced with 145°C. That is, during the lamination thermal curing process, the temperature of the first stage of thermal curing is the same as that of the second stage of thermal curing, and the other steps remain unchanged.
[0113] Application Example 9
[0114] This application example provides a photovoltaic module, which differs from application example 1 only in that the temperature of the second stage of thermal curing in step (4) is replaced with 200°C when preparing the photovoltaic module, while the other steps remain unchanged.
[0115] Comparative Application Example 1
[0116] This comparative application example provides a photovoltaic module. The difference between the preparation method of the photovoltaic module and that of application example 1 is that the raw material for preparing the insulating adhesive in step (2) of example 1 is replaced with the raw material for preparing the insulating adhesive described in comparative example 1, while the other preparation steps remain unchanged.
[0117] Comparative Application Example 2
[0118] This comparative example provides a photovoltaic module, which differs from Application Example 1 only in that step (1) does not involve plasma cleaning, but only conventional wiping, while the other preparation steps remain unchanged.
[0119] Comparative Application Example 3
[0120] This comparative example provides a photovoltaic module, which differs from Application Example 1 only in that the degree of curing of the insulating adhesive in step (3) is 95%, and the lamination thermal curing in step (4) is not performed, while the other preparation steps remain unchanged.
[0121] test:
[0122] The photovoltaic modules prepared in the corresponding use cases and comparative application examples were tested under the following conditions:
[0123] Surface energy of solar cells: Using a contact angle meter and the OWRK method (Owens-Wendt-Rabel-Kaelble method), with water and diiodomethane as the test liquids, the contact angles of the two on the surface of the solar cells were measured respectively, and the surface energy (unit: dynes) was calculated by the OWRK equation.
[0124] Initial peel strength: Referring to GB / T 2790-1995 "Adhesives - Test Method for 180° Peel Strength (Flexible Materials vs. Rigid Materials)," a universal tensile testing machine was used to test the peel strength (unit: N / cm) between the insulating adhesive layer and the BC solar cell at a peel angle of 180° and a peel speed of 50 mm / min. The average value of 5 test points was taken for each sample.
[0125] Peel strength after 85 aging: The photovoltaic module was placed in a constant temperature and humidity chamber at 85℃ and 85%RH for 1000 hours of aging. After that, it was taken out and equilibrated at room temperature (23±2℃) for 24 hours. Then, a 180° peel test was performed under the same test conditions as the initial peel strength.
[0126] Peel strength retention rate: Retention rate (%) = (Peel strength after 1000 hours of aging with double 85 / Initial peel strength) × 100%.
[0127] The test results are shown in Table 1 below.
[0128] Table 1
[0129]
[0130] The test results show that:
[0131] (1) As can be seen from Application Examples 1-3, this application uses a block copolymer and / or high and low Tg resin blend system as the main resin of the insulating adhesive, combined with the preparation strategy of "plasma activation pretreatment + UV pre-curing + lamination thermal curing", which significantly improves the adhesion of the insulating adhesive to the back of the cell after aging. After undergoing double 85 aging test (85℃ / 85%RH) or thermal cycling aging, the insulating adhesive layer and the cell interface did not delaminate, thus improving the long-term reliability and power generation efficiency of the photovoltaic module.
[0132] (2) By comparing Application Example 1 with Application Examples 4-5, it can be seen that this application further controls the mass ratio of high Tg resin to low Tg resin to be 1:(0.8-1.2). The mass ratio of high Tg resin to low Tg resin affects the microphase continuity and stress transfer efficiency of the blend system. When the content of high Tg resin is too high (Application Example 4, high Tg: low Tg = 1:0.5, the proportion of high Tg is too high), the system is too rigid, the low Tg resin cannot form a continuous flexible dispersed phase, the stress relaxation ability under lamination high temperature is insufficient, the initial peel strength drops from 70 N / cm to 58 N / cm, and the peel strength retention rate after double 85 aging is only 43.1%, which is much lower than the 71.4% of Application Example 1. When the content of high-Tg resin is too low (Application Example 5, high-Tg:low-Tg = 1:2, low-Tg proportion is too high), the overall cohesive strength of the system is insufficient, and the initial peel strength drops to 55 N / cm. Although the low-Tg component provides some stress relaxation, the retention rate after aging is only 54.5%, lower than that of Application Example 1. Therefore, only when the mass ratio of the two is controlled within the range of 1:(0.8-1.2) can a good balance between the rigid network and the flexible dispersed phase be achieved, taking into account both initial strength and adhesion retention rate after aging.
[0133] (3) By comparing Application Example 1 with Application Examples 6-7, it can be seen that this application further controls the irradiation energy density during the UV pre-curing process to 400 mJ / cm². 2 -800mJ / cm 2The irradiation energy density during the UV pre-curing process affects the decomposition efficiency of the photoinitiator and the rate of free radical generation, thus determining the intermediate degree of curing and the subsequent thermosetting reaction window. When the UV energy density is too low (Application Example 6, 300 mJ / cm²), the irradiation energy density is significantly reduced. 2 When the actual degree of curing is approximately 48%, the photoinitiator decomposes insufficiently, the free radical concentration is too low, the intermediate curing degree is insufficient, the surface drying effect of the adhesive layer is poor, the cohesive strength is extremely low, the initial peel strength is only 48 N / cm, and the liquid component is prone to overflow during subsequent lamination, with a retention rate of only 37.5% after aging. When the UV energy density is too high (Application Example 7, 900 mJ / cm), 2 When the actual degree of curing is approximately 80%, the photoinitiator decomposes excessively, resulting in an excessively high conversion rate of C=C double bonds and premature formation of a highly cross-linked rigid network. A significant amount of shrinkage stress cannot be released subsequently, and the thermosetting functional monomers are trapped within the dense network, making it difficult to migrate to the interface reaction. Although the initial peel strength reaches 72 N / cm, it drops sharply to 32 N / cm after aging, with a retention rate of only 44.4%. Therefore, the UV pre-curing energy density must be controlled at 400 mJ / cm². 2 -800mJ / cm 2 This ensures that the intermediate curing degree is 60%-70%, which meets the production line's anti-disturbance requirements while reserving a sufficient chemical bonding reaction window for subsequent thermal curing.
[0134] (4) By comparing Application Example 1 with Application Examples 8-9, it can be seen that this application further controls the lamination thermosetting process by dividing it into two stages of heating, and controls the temperature of the first stage thermosetting to 90℃-120℃ and the second stage to 130℃-150℃. The thermosetting temperature of different stages affects the unsealing rate and degree of the blocked isocyanate, the stress relaxation effect of the low Tg resin, and the interfacial chemical bonding efficiency. When the temperature of the first stage is too high (Application Example 8, directly using 145℃), the blocked isocyanate is prematurely and extensively unsealed in the first stage. At this time, the encapsulating film has not yet fully melted and flowed, and the insulating adhesive layer has not fully wetted the interfacial microstructure at a lower temperature. Chemical bonding occurs prematurely in the state of "insufficient interfacial contact", the effective bonding density is low, the initial peel strength drops from 70N / cm to 62N / cm, and the retention rate after aging is only 45.2%. When the temperature in the second stage is too high (Application Example 9, 200℃), although the unsealing rate is accelerated, the polyester resin and polyester acrylate undergo thermal oxidative degradation at high temperatures, resulting in molecular chain breakage and decreased cohesive strength. Simultaneously, the encapsulating film (EVA) decomposes, generating volatile gases that create interfacial voids. The initial peel strength is only 60 N / cm, and the retention rate after aging is only 33.3%. Therefore, the first-stage temperature should be controlled at 90-120℃ to achieve sufficient wetting and initial stress release, while the second-stage temperature should be controlled at 130-150℃ to achieve sufficient chemical bonding and avoid thermal degradation. This two-stage gradient heating strategy is key to achieving high aging adhesion.
[0135] (5) As can be seen from Application Example 1 and Comparative Application Example 1, this application achieves a synergistic mechanical effect of "combining rigidity and flexibility" by introducing a blend of low-Tg resin and high-Tg resin as the main resin. Although Comparative Application Example 1 also underwent plasma cleaning (surface energy > 65 dynes), it only contained high-Tg resin (polyester acrylate) and no low-Tg resin (polyester resin), and its initial peel strength was only 42 N / cm, significantly lower than the 70 N / cm of Application Example 1; after aging at 85 for 1000 hours, the peel strength dropped sharply to 15 N / cm, with a retention rate of only 35.7%. Cross-sectional analysis showed that the adhesive layer became stiff and brittle, and microcracks were generated under thermal cycling stress, leading to interface failure. This indicates that relying solely on plasma activation and UV curing, without the stress relaxation mechanism of the low-Tg resin component, it is impossible to maintain high adhesion during the aging process.
[0136] (6) As can be seen from Application Example 1 and Comparative Application Example 2, the surface energy of the battery cell after conventional solvent wiping is low, only 38 dynes, and the initial peel strength is 28 N / cm, which is much lower than 70 N / cm in Application Example 1. After 1000 hours of dual 85 aging, the peel strength drops to 8 N / cm, and the retention rate is only 28.6%. Obvious fingerprint-like residue patterns were found at the failure interface, confirming that surface contaminants hindered the direct bonding between the adhesive and the substrate, leading to hydrolytic failure of the contaminant interface during aging. This indicates that the plasma cleaning process used in this application is a necessary prerequisite for ensuring long-term reliability.
[0137] (7) As can be seen from Application Example 1 and Comparative Application Example 3, when only UV curing is performed to achieve a curing degree of over 95% without lamination thermosetting, the thermosetting functional monomer (blocked isocyanate) is never deblocked, the -NCO groups cannot be released, and cannot covalently bond with the -OH introduced by plasma cleaning. The interfacial bonding relies only on physical adsorption and a small amount of hydrogen bonding. At the same time, the low Tg resin has not undergone high-temperature softening and cannot fully wet the micro-uneven structure on the back of the battery cell. There are a large number of micropores at the interface, where moisture easily accumulates and accelerates hydrolysis failure. The initial peel strength was 52 N / cm, and after 1000 hours of double 85 aging, the peel strength dropped sharply to 10 N / cm, with a retention rate of only 19.2%. This shows that UV curing can only achieve rapid shaping of the adhesive layer, while lamination thermosetting is the key process to achieve chemical bonding, full wetting, and stress relaxation. Both are indispensable.
[0138] In summary, this application significantly improves the adhesion of the insulating adhesive to the back of the solar cell after aging by using a block copolymer and / or high and low Tg resin blend system as the main resin of the insulating adhesive, combined with the preparation strategy of "plasma activation pretreatment + UV pre-curing + lamination thermosetting". After undergoing double 85 aging test (85℃ / 85%RH) or thermal cycling aging, no delamination occurred between the insulating adhesive layer and the solar cell interface, thus improving the long-term reliability and power generation efficiency of the photovoltaic module.
[0139] The applicant declares that the above description is only a specific implementation of this application, but the protection scope of this application is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in this application fall within the protection and disclosure scope of this application.
Claims
1. An insulating adhesive, characterized in that, The raw materials for preparing the insulating adhesive include a base resin, an active diluent, a thermosetting functional monomer, an adhesion promoter, an inorganic filler, a photoinitiator, a silane coupling agent, and additives. The main resin includes a block copolymer and / or a blend system of high and low Tg resins; The high- and low-Tg resin blend system includes high-Tg resin and low-Tg resin.
2. The insulating adhesive according to claim 1, characterized in that, The high Tg resin includes any one or a combination of at least two of pentaerythritol pentaacrylate, trimethylolpropane triacrylate, or pentaerythritol tetraacrylate. And / or, the low Tg resin includes any one or a combination of at least two of polyethylene adipate diol, polycaprolactone diol, or polycarbonate diol; And / or, the mass ratio of the high Tg resin to the low Tg resin is 1:(0.8-1.2).
3. The insulating adhesive according to claim 1 or 2, characterized in that, Based on a total mass of 100wt% of the raw materials used to prepare the insulating adhesive, the main resin accounts for 40.0wt%-80.0wt%, the reactive diluent accounts for 5.0wt%-15.0wt%, the thermosetting functional monomer accounts for 5.0wt%-15.0wt%, the adhesion promoter accounts for 3.0wt%-8.0wt%, the inorganic filler accounts for 2.0wt%-6.0wt%, the photoinitiator accounts for 1.0wt%-4.0wt%, the silane coupling agent accounts for 0.5wt%-2.0wt%, and the additives account for 0.5wt%-2.0wt%.
4. The insulating adhesive according to any one of claims 1-3, characterized in that, The block copolymer includes any one or a combination of at least two of the following: polystyrene-block-polybutadiene-block-polystyrene, polystyrene-block-polyisoprene-block-polystyrene, polystyrene-block-poly(ethylene-butene)-block-polystyrene, polystyrene-block-poly(ethylene-propylene)-block-polystyrene, or polyurethane-block-polyether copolymer; And / or, the reactive diluent includes isobornyl acrylate; And / or, the thermosetting functional monomer comprises a blocked isocyanate with a desealing temperature >180°C; And / or, the adhesion promoter includes polyethylene glycol monomethacrylate phosphate; And / or, the inorganic filler comprises hydrophobic fumed silica; And / or, the photoinitiator comprises 2,4,6-trimethylbenzoyldiphenylphosphine oxide; And / or, the silane coupling agent comprises KH-570 and / or aminosilane; And / or, the additives include isophorone leveling agents and / or fatty acid ester defoamers.
5. A method for preparing an insulating adhesive as described in any one of claims 1-4, characterized in that, The preparation method includes the following steps: The raw materials for preparing the insulating adhesive according to any one of claims 1-4 are first subjected to UV pre-curing to obtain an intermediate state of the insulating adhesive; The insulating adhesive is obtained by laminating and thermosetting the intermediate state of the insulating adhesive; The degree of curing of the insulating adhesive in its intermediate state is 60%-70%.
6. The preparation method according to claim 5, characterized in that, The wavelength of the UV light used in the UV pre-curing is 365nm-395nm; And / or, the irradiation energy density during the UV pre-curing process is 400 mJ / cm². 2 -800mJ / cm 2 .
7. The preparation method according to claim 5 or 6, characterized in that, The lamination thermosetting includes a first-stage thermosetting and a second-stage thermosetting; And / or, the pressure during the lamination thermosetting process is 10 kPa-70 kPa; And / or, the temperature for the first stage of thermosetting is 90℃-120℃; And / or, the time for the first stage of thermosetting is 3 min-6 min; And / or, the temperature for the second stage of thermosetting is 130℃-150℃; And / or, the second stage of thermosetting time is 5 min-10 min.
8. A photovoltaic module, characterized in that, The photovoltaic module includes the insulating adhesive as described in any one of claims 1-4 or the insulating adhesive prepared by the preparation method described in any one of claims 5-7.
9. A method for preparing a photovoltaic module as described in claim 8, characterized in that, The preparation method includes the following steps: (1) Plasma cleaning of BC solar cells; (2) The raw material for preparing the insulating adhesive according to any one of claims 1-4 is disposed on the back side of the cleaned BC battery cell; (3) UV pre-curing of the raw materials for preparing the insulating adhesive to obtain an intermediate state of insulating adhesive with a curing degree of 60%-70%, and then setting photovoltaic welding ribbons to obtain BC cell strings; (4) The BC battery string is encapsulated and then laminated and thermocured to obtain the photovoltaic module.
10. The preparation method according to claim 9, characterized in that, The plasma cleaning uses an argon-oxygen mixture; And / or, the volume ratio of argon to oxygen in the argon-oxygen mixture is (90-95):(5-10); And / or, the vacuum degree of the plasma cleaning is 10Pa-20Pa; And / or, the power of the plasma cleaning is 150W-250W; And / or, the plasma cleaning time is 45s-90s.
